The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.13102/sociobiology.v67i3.5083
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of the Ant Genus Neoponera Emery, 1901 (Formicidae: Ponerinae) in the north of the Brazilian Atlantic Forest, with new Records of Occurrence

Abstract: Composed of two main forest formations, Ombrophilous Forest and Seasonal Forest, the Brazilian Atlantic Forest biome is constituted currently by a mosaic of forest remnants and secondary vegetation. Representatives of the Ponerinae ant genus Neoponera are observed mainly in both wet and seasonally dry forests. The aim of this study was to approach the diversity of the genus Neoponera in the north of the Atlantic Forest of Brazil (from the extreme north of its distribution to the Doce River hydrographic basin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In recent years, great advances have been made in this kind of study, allowing inferring the history of distribution based on phylogenetic analyzes, such as on Myrmicinae (Ward et al, 2014). A range of taxonomic studies by biogeographical regions (Ladino & Feitosa, 2020), new occurrences, and records (Dias & Lattke, 2019;Fernandes & Delabie, 2019;Franco, et al, 2019), invasive species (Chen & Adams, 2018), and diversity (Koch et al, 2020;Silva et al, 2020) can also be found. In addition, modeling distribution studies on Formicidae have gained space, under the following names and techniques: potential distribution modeling (Murphy & Breed, 2007;Koch et al, 2018), niche modeling (Peterson & Nakazawa, 2007), paleodistribution (Cristiano et al, 2016), and projections of future scenarios (Jung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, great advances have been made in this kind of study, allowing inferring the history of distribution based on phylogenetic analyzes, such as on Myrmicinae (Ward et al, 2014). A range of taxonomic studies by biogeographical regions (Ladino & Feitosa, 2020), new occurrences, and records (Dias & Lattke, 2019;Fernandes & Delabie, 2019;Franco, et al, 2019), invasive species (Chen & Adams, 2018), and diversity (Koch et al, 2020;Silva et al, 2020) can also be found. In addition, modeling distribution studies on Formicidae have gained space, under the following names and techniques: potential distribution modeling (Murphy & Breed, 2007;Koch et al, 2018), niche modeling (Peterson & Nakazawa, 2007), paleodistribution (Cristiano et al, 2016), and projections of future scenarios (Jung et al, 2017).…”
Section: Introductionmentioning
confidence: 99%